Transformasi Fondasi Iman Kristen dalam Pelayanan Pastoral di Era Society 5.0 - Joko Santoso; Seri Damarwanti; I Made Priana; Teguh Bowo Sembodo; Anthoneta Taru PA (Sekolah Tinggi Teologi Berita Hidup, 2021)
In the Era of Society 5.0, it is very important for the church to lay down the foundation of Christian Faith for Pastoral Services in answering the problems of God's people and in solving various life challenges include social problems through the use of various information and communication technology innovations accompanied by the development of an era of disruption such as the Internet (Internet on Things), Intelligence artificial intelligence (Artificial Intelligence), and Data Banks (Big Data). This research is conducted to answer the issue of how pastoral care is contextually working in today's digital world, which also influences changes in life styles and thus demands an adaptive pastoral care approach without losing the essence of pastoral care itself. This study proposes a foundation of Christian Faith in creative and innovative pastoral care. The research method uses a literature study approach whereas coclusion can be drawn that creative and innovative pastoral care must be done by laying the foundation for a realistic theological pastoral ministry in facing the challenges of the times. The newness of the research compared to previous similar studies lies in how the era of society 5.0 brings a new paradigm of the importance of the humanistic side to be a priority and basis, besides the need to maintain the essence of pastoral care itself.Gereja di Era Society 5.0 sangat penting meletakkan Dasar Pondasi Iman Kristen Pelayanan Pastoral guna menjawab persoalan umat Tuhan dalam menyelesaikan berbagai tantangan hidup termasuk permasalahan sosial melalui pemanfaatan berbagai inovasi teknologi informasi dan komunikasi yang dibarengi adanya perkembangan era disrupsi seperti Internet (Internet on Things), Kecerdasan buatan (Artificial Intelligence), dan Bank Data (Big Data). Penelitian ini dilakukan untuk menjawab issue bagaimana Pelayanan Pastoral semakin kontekstual dalam dunia digital sekarang, yang turut mempengaruhi perubahan tatanan dan gaya hidup sehingga menuntut pendekatan pelayanan pastoral yang adaptif tanpa perlu kehilangan esensi pelayanan pastoral itu sendiri. Kajian ini mengusulkan pondasi Iman Kristen dalam pelayanan pastoral yang kreatif dan inovatif. Metode penelitian menggunakan pendekatan studi literatur untuk menarik kesimpulan bahwa pelayanan pastoral yang kreatif dan inovatif dimulai dengan meletakkan dasar pondasi pelayanan pastoral yang realistis teologis dalam menyingkapi tantangan zaman. Keterbaharuan penelitian dibandingkan dengan penelitian sejenis sebelumnya terletak pada bagaimana era society 5.0 membawa paradigma baru pentingnya sisi humanistis menjadi prioritas dan dasar, disamping perlunya tetap menjaga esensi pelayanan pastoral itu sendiri.